2000
DOI: 10.1111/1468-2419.00099
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder involvement in strategic HRD aligning: the impact on HRD effectiveness

Abstract: The study reported here focusses on the question to what extent stakeholder involvement in HRD policymaking (here referred to as strategic HRD aligning) predicts effective HRD programmes. The study involved 44 large companies in the industrial, financial and commercial services sectors. The findings indicate that involvement of stakeholders in the strategic HRD aligning process, and their opinions on the quality of this aligning process in particular, have a positive effect on perceived HRD effectiveness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…These findings could be useful for building a bridge between the programme evaluation and human resource development (HRD) fields. This bridge may be strategic, considering the importance of training evaluation, which continues to be essential in demonstrating the added value of HRD, and the fact that the involvement of stakeholders in the strategic HRD aligning process has a positive effect on its effectiveness (Wognum & Lam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be useful for building a bridge between the programme evaluation and human resource development (HRD) fields. This bridge may be strategic, considering the importance of training evaluation, which continues to be essential in demonstrating the added value of HRD, and the fact that the involvement of stakeholders in the strategic HRD aligning process has a positive effect on its effectiveness (Wognum & Lam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…While assuming a more strategic role within the organization is a continuous challenge for performance improvement professionals, research has shown that the perception of their utility is increased when stakeholders are aware of how performance interventions align with organizational goals (Wognum & Lam, 2000). In particular, performance improvement professionals can demonstrate their value in crisis planning by (1) informing stakeholders of crisis planning research, resources, and processes; (2) using performance improvement tools (such as the HPT model) to assess crisis vulnerabilities in individuals and systems; and (3) designing performance interventions that align with organizational goals to enhance individual, team, and organizational crisis preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers considering SHRD‐alignment perspectives have also noted the importance of ensuring that organizational‐level and human resource needs are considered as valuable inputs to designing strategy (Buller & McEvoy, ). SHRD‐alignment researchers have noted concern that the human needs and the “whole person” perspective are not forgotten when determining strategies for achieving and maintaining a competitive advantage in the marketplace (Alagaraja & Shuck, ; Campbell, Coff, & Kryscynski, ; Wognum & Fond Lam, ; Wright & McMahan, ).…”
Section: Shrd Alignment: An Overview Of the Literaturementioning
confidence: 99%
“…However, researchers considering SHRD-alignment perspectives have also noted the importance of ensuring that organizational-level and human resource needs are considered as valuable inputs to designing strategy (Buller & McEvoy, 2012). SHRD-alignment researchers have noted concern that the human needs and the "whole person" perspective are not forgotten when determining strategies for Volume 31, Number 3 / 2018 DOI: 10.1002/piq 273 achieving and maintaining a competitive advantage in the marketplace (Alagaraja & Shuck, 2015;Campbell, Coff, & Kryscynski, 2012;Wognum & Fond Lam, 2000;Wright & McMahan, 2011). An important component in all models of SHRD alignment takes into account the employee's perspective, which is closely linked with various aspects of an organization's learning culture (e.g., individual-level continuous learning, open-dialog components) (Leufvén, Vitrakoti, Bergström, Ashish, & Målqvist, 2015;Marsick & Watson, 2003).…”
Section: Employee Line Of Sightmentioning
confidence: 99%